Optimizing Efficiency, Effectiveness, and Quality of Scholarly Output through Artificial Intelligence - Mundir, Mundir; As’ari, As’ari (Universitas Nurul Jadid, 2026)
Undergraduate students at the Faculty of Tarbiyah and Teacher Training, State Islamic University Kiai Haji Achmad Siddiq Jember frequently encounter difficulties in preparing thesis proposals, including weak problem formulation, misalignment between research topics and theoretical frameworks, limited academic literacy, and inadequate reference management. At the same time, the rapid development of Artificial Intelligence (AI) tools presents both opportunities and ethical challenges in academic writing. This community engagement program aimed to strengthen students’ competencies in using AI ethically and effectively to support the preparation of research proposals. The program involved 35 undergraduate students and was conducted over four weeks using a service-learning model integrated with transformative learning principles. The activities were implemented through three stages: interactive workshops (IN), AI-assisted proposal development (OUT), and proposal presentation and reflection (IN). Program evaluation employed proposal completion records, observations, and a Likert-scale questionnaire measuring effectiveness, efficiency, and writing quality. The results show that 31 of 35 students (89%) successfully produced AI-assisted research proposals, while 4 students (11%) did not complete their proposals. Questionnaire findings indicate that 71% of students strongly agreed that AI improved writing effectiveness, 77% strongly agreed that it increased efficiency, and 63% strongly agreed that it enhanced writing quality. These findings indicate that structured training enables students to use AI as a supportive academic tool while maintaining ethical awareness and academic integrity in scholarly writing.